2010
DOI: 10.1002/ajim.20811
|View full text |Cite
|
Sign up to set email alerts
|

Farm work exposure of older male farmers in Saskatchewan

Abstract: The amount of hours older farmers work on the farm is considerable compared to any other occupational category. While there is a declining trend in the amount of work, a 75-year-old farmer still works, on average, about 34 hr per week. Some farmers do appear to self-limit during busy times of the year if they are taking medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…In our previous analysis [Voaklander et al, 2010], we confirmed previous work [Lizer and Petrea, 2007] that suggests that older farmers work similar long hours when compared to their younger counterparts. We also reported that there was little accommodation of work exposure for self‐reported health conditions.…”
Section: Introductionsupporting
confidence: 90%
“…In our previous analysis [Voaklander et al, 2010], we confirmed previous work [Lizer and Petrea, 2007] that suggests that older farmers work similar long hours when compared to their younger counterparts. We also reported that there was little accommodation of work exposure for self‐reported health conditions.…”
Section: Introductionsupporting
confidence: 90%
“…However, unlike associations identified in the US [23,24], this increase in the Australian data was not statistically significant. While the proportion of farmers over 50 years of age increased in this period, there was an overall reduction in total numbers by 8.52% (approximately 0.57% per annum) [8]. Hence, the increase in rates is unlikely to be simply attributed to larger numbers of farmers 50 years of age and over being exposed.…”
Section: Discussionmentioning
confidence: 92%
“…Medication use has been raised as a potential contributing factor to injuries in older farmers [8]. For this sample, it appeared to have a limited impact with only three cases reporting the presence of prescription medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chronic health problems have only a minor impact on the number of hours worked on the farm (Marcum et al, 2011a). Older farmers carry workloads similar to their younger counterparts, working as much as 10 or 12 hours per day (Lizer and Petrea, 2007;Marcum et al, 2011a;Reed et al, 2012;Voaklander et al, 2010). Despite changes in their physical and mental abilities, senior farmers continue to work with a general attitude that the potential for injury is a normal part of their occupation (McLaughlin and Sprufera, 2011).…”
mentioning
confidence: 99%